High Quality Paper award IEEE PES 2019 PowerTech - Aristidou, Petros (My University, 2026)
High-Quality Paper award for paper ’Data-driven Control Design Schemes in Active Distribution Grids: Capabilities and Challenges’, IEEE PES 2019 PowerTech, Milan (honorary diploma) Role: co-author
Keywords: Sciences